A Database of Laboratory Analogue Models of Caldera Collapse Testing the Role of Inherited Structures - Maestrelli, Daniele; Bonini, Marco; Corti, Giacomo; Del Ventisette, Chiara; Moratti, Giovanna; Montanari, Domenico (Frontiers in Earth Science, 2021)
Since caldera collapse deformation is extremely difficult to study in real time - due to the high deformation rates that characterize this process and the difficult access to the caldera structures-analogue modeling has been widely used during past decades to integrate field data and, more recently, remote-sensing data (e.g., InSAR). However, the relationships between caldera collapse and inherited discontinuities, such as inherited crustal faults, remain poorly investigated. We therefore provide a new dataset of analogue models that aims to specifically address this issue and that can be potentially compared with literature and natural case studies worldwide. We present a dataset of 13 analogue models of caldera collapse investigating the interactions between caldera collapse processes and inherited crustal discontinuities. The dataset is composed of raw data and elaborations that can be used to qualitatively visualize and/or quantitatively analyze model deformation through the use of top-view photos, digital elevation models (DEM) and digital particle image velocimetry (DPIV).